(untitled) (Revista Innova Educación, 2019)
The purpose of this research was to determine the degree of relationship between Knowledge Management and Job Satisfaction in teachers of the educational institutions of the Initial level of the city of Puno. The research corresponds to the basic type, is descriptive and with a correlational design, the study sample constituted 64 teachers from the educational institutions of the Initial Education level, the information was collected with the survey technique and as an instrument the questionnaire. It is concluded that, the degree of relationship between Knowledge Management and Job Satisfaction in teachers of the educational institutions of the Initial level of the city of Puno in 2016 is positive, according to the Zc test that was 3.42 accepting the alternative hypothesis (Hi), the frequency of Knowledge Management is almost always, according to 44% of teachers; while, the frequency of Job Satisfaction is from time to time, according to 40% of teachers surveyed.